Positive electrode active material, its manufacturing method and lithium secondary battery including same
Patent Information
- Application Number
- JP2023538657
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-12-21
- Filing Date
- 2021-12-20
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2041-12-20
AI Technical Summary
【0023】 本発明の一実施例による正極活物質は、コート層にW、Nbなどの5族または6族元素とB、LiOH、Li2CO3およびLi2SO4をすべて含むので、正極活物質の高容量を確保することができ、高温寿命の特性に優れ、初期抵抗および抵抗増加率を顕著に減少させることができる。
Smart Images

Figure 0007629998000004 
Figure 0007629998000005 
Figure 0007629998000006
Abstract
Description
[Technical field]
[0001] The present invention relates to a positive electrode active material, a manufacturing method thereof, and a lithium secondary battery including the same. More specifically, the present invention relates to a positive electrode active material including at least one of Group 5 elements and Group 6 elements, B, LiOH, Li2CO3, and Li2SO4 in a coating layer located on the surface of lithium metal oxide particles, a manufacturing method thereof, and a lithium secondary battery including the same. [Background technology]
[0002] Recently, there has been an explosive increase in demand for IT mobile devices and small power-driven devices (e-bikes, small EVs, etc.), as well as a need for electric vehicles with a driving range of 400 km or more. In response to this, the development of high-capacity, high-energy density secondary batteries to power these devices is being actively pursued worldwide.
[0003] To manufacture such high-capacity batteries, high-capacity positive electrode materials must be used. The currently available layered positive electrode active material with the highest capacity is LiNiO2 (275mAh / g), but it is difficult to commercialize due to its tendency to collapse during charging and discharging and its low thermal stability due to its oxidation number.
[0004] To solve these problems, we developed an NCM-based positive electrode active material that improves electrochemical stability by substituting different transition metals (Co, Mn, etc.) on the Ni site. Summary of the Invention [Problem to be solved by the invention]
[0005] The present invention provides a positive electrode active material, a method for producing the same, and a lithium secondary battery including the same. More specifically, the present invention provides a positive electrode active material including at least one of Group 5 elements and Group 6 elements, B, LiOH, Li2CO3, and Li2SO4 in a coating layer located on the surface of lithium metal oxide particles, a method for producing the same, and a lithium secondary battery including the same. [Means for solving the problem]
[0006] A positive electrode active material for a lithium secondary battery according to an embodiment includes lithium metal oxide particles; and a coating layer located on at least a portion of a surface of the lithium metal oxide particles, and the coating layer may include any one or more of a Group 5 element and a Group 6 element, B, LiOH, Li2CO3, and Li2SO4.
[0007] The positive electrode active material may be in the form of secondary particles including a plurality of primary particles, and at least one of the Group 5 element and the Group 6 element may be located on at least a portion of the surface of the primary particles.
[0008] The Group 5 element may include Nb.
[0009] The Group 6 element may include W.
[0010] The content of the Group 5 element and the Group 6 element may be in the range of 10 ppm to 10,000 ppm based on the entire positive electrode active material.
[0011] The content of LiOH may be in the range of 100 ppm to 10,000 ppm based on the total amount of the positive electrode active material.
[0012] The content of Li2SO4 may be in the range of 10 ppm to 3000 ppm based on the total amount of the positive electrode active material.
[0013] The Li2CO3 may be produced by an internal reaction rather than being added separately as a lithium raw material.
[0014] In the positive electrode active material, when analyzed by XPS, there may be a peak near 192.1 eV and a peak near 195.0 eV, and there may be a peak near 35.0 eV and a peak near 38.5 eV.
[0015] In the positive electrode active material, a ratio of relative intensities of Ni and W present at the boundaries of the primary particles may satisfy the following formula 1 when analyzed by EDS:
[0016] [Formula 1] 0.1≦[I Ni / I W ]≦2.0 (Here, I Ni is the relative intensity of Ni at the boundary of the primary particle, I W means the relative intensity of W present at the boundary of the primary particle.)
[0017] The nickel content in the metals within the lithium metal oxide particles may be 85 mol % or more.
[0018] According to another embodiment, a method for manufacturing a positive electrode active material for a lithium secondary battery includes: introducing a metal salt aqueous solution into a co-precipitation reactor to obtain a metal precursor; mixing the metal precursor, a lithium source material, and a doping source material to prepare a mixture; performing a first heat treatment on the mixture and then cooling it; washing the product obtained in the cooling step with a material containing at least one of a Group 5 element and a Group 6 element; and drying the washed product, mixing it with a coating layer forming material, and performing a second heat treatment on the product; the coating layer forming material may include a boron compound, LiOH, and Li2SO4.
[0019] In the water washing step, the material containing a Group 5 element may be a mixture of at least one of distilled water and alcohol; and at least one of ammonium niobium oxalate, niobium oxide, niobium nitride, niobium boride, niobium pentaethoxide, niobium i-propoxide, niobium n-propoxide, niobium i-butoxide, niobium n-butoxide, niobium halide, and niobium nitrate.
[0020] In the water washing step, the Group 6-containing material may be a mixture of at least one of distilled water and alcohol; and at least one of ammonium meta-tungstate (AMT), ammonium para-tungstate, tungsten oxide, tungsten halide, tungsten hexaethoxide, tungsten i-propoxide, tungsten boride, tungsten nitride, and tungsten carbonyl.
[0021] The second heat treatment may be performed at a temperature in the range of 200 to 450°C.
[0022] A lithium secondary battery according to another embodiment may include a positive electrode including a positive electrode active material according to an embodiment; a negative electrode; and a non-aqueous electrolyte. Effect of the Invention
[0023] The positive electrode active material according to one embodiment of the present invention contains a Group 5 or Group 6 element, such as W or Nb, and B, LiOH, Li2CO3, and Li2SO4 in the coating layer, so that the positive electrode active material can have high capacity, excellent high-temperature life characteristics, and significantly reduced initial resistance and resistance increase rate. [Brief description of the drawings]
[0024] [Figure 1] 1 is a TEM / EDS analysis photograph of the positive electrode active material of Example 1. [Diagram 2] 1 is a cross-sectional EDS line profile image of the positive electrode active material of Example 1. [Diagram 3] FIG. 2 is a diagram showing an XPS analysis of the positive electrode active material of Example 1. [Figure 4] FIG. 1 is a graph showing the change in discharge capacity depending on the W content in Example 1 and Examples 2-1 to 2-6. [Diagram 5] FIG. 1 is a graph showing DC-IR changes depending on the W content in Example 1 and Examples 2-1 to 2-6. [Figure 6] FIG. 1 is a graph showing the change in DCIR increase rate depending on the W content in Example 1 and Examples 2-1 to 2-6. [Figure 7] FIG. 1 is a graph showing the initial discharge capacity as a function of the LiOH content in Example 1 and Examples 4-1 to 4-4. [Figure 8] FIG. 1 is a graph showing the change in discharge capacity depending on the Li2SO4 content in Example 1 and Examples 3-1 to 3-5. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0025] In this specification, the terms first, second, and third are used to describe various parts, components, regions, layers, and / or sections, but are not limited thereto. These terms are used to distinguish one part, component, region, layer, or section from another part, component, region, layer, or section. Thus, a first part, component, region, layer, or section described below may be referred to as a second part, component, region, layer, or section without departing from the scope of the present invention.
[0026] In this specification, when a part is said to "comprise" a certain component, this means that it may further include other components rather than excluding other components, unless specifically stated to the contrary.
[0027] The terminology used in this specification is merely for the purpose of referring to particular embodiments and is not intended to limit the present invention. As used herein, the singular form includes the plural form unless the context clearly indicates otherwise. The term "comprising" as used in this specification refers to the specific features, regions, integers, steps, operations, elements and / or components and does not exclude the presence or addition of other features, regions, integers, steps, operations, elements and / or components.
[0028] In this specification, the term "combinations thereof" included in a Markush form expression means a mixture or combination of one or more selected from the group consisting of the components described in the Markush form expression, and means including one or more selected from the group consisting of the components.
[0029] As used herein, when a moiety is referred to as being "on" or "on" another moiety, this means that it is directly on or above the other moiety, or there may be other moieties between them. In contrast, when a moiety is referred to as being "directly on" another moiety, there are no other moieties between them.
[0030] Unless otherwise defined, all terms, including technical and scientific terms, used herein have the same meaning as commonly understood by a person of ordinary skill in the art to which the present invention belongs. Terms defined in commonly used dictionaries are further analyzed as having a meaning that fits the relevant technical literature and the present disclosure, and are not interpreted as being overly ideal or formal unless otherwise defined.
[0031] Moreover, unless otherwise specified, % means % by weight, and 1 ppm is 0.0001% by weight.
[0032] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The present invention will now be described in detail with reference to exemplary embodiments thereof, so that those skilled in the art can easily practice the present invention. However, the present invention may be embodied in many different forms and should not be construed as limited to the embodiments set forth herein.
[0033] According to one embodiment, a positive electrode active material for a lithium secondary battery includes lithium metal oxide particles and a coating layer located on at least a portion of a surface of the lithium metal oxide particles, the coating layer including at least one of a Group 5 element and a Group 6 element, B, LiOH, Li2CO3, and Li2SO4.
[0034] More specifically, the lithium metal oxide particles may have a layered structure, and a coating layer containing at least one of group 5 and group 6 elements, B, LiOH, Li2CO3, and Li2SO4 is located on the surface of the particles, thereby reducing the resistance of the surface of the positive electrode active material. As a result, the capacity can be increased and the life characteristics at high temperatures can be improved. In addition, there is an advantage in that the initial resistance and the rate of increase in resistance at high temperatures can be significantly reduced.
[0035] More specifically, at least one of the Group 5 elements and Group 6 elements is coated by a first wet coating, and B, LiOH, Li2CO3 and Li2SO4 are coated by a second dry coating.
[0036] That is, the cathode active material according to an embodiment of the present invention is in the form of secondary particles including a plurality of primary particles, and at least one of the Group 5 element and the Group 6 element may be located on at least a portion of the surface of the primary particles. In this case, the Group 5 element may be Nb and the Group 6 element may be W.
[0037] On the other hand, the positive electrode active material of this embodiment contains at least five elements or compounds in the coating layer as described above, and therefore can exhibit a synergistic effect.
[0038] In this embodiment, the content of the Group 5 element and the Group 6 element may be in the range of 10 ppm to 10000 ppm, more specifically 30 ppm to 5000 ppm, even more specifically 80 ppm to 2000 ppm, and even more specifically 300 ppm to 800 ppm based on the total amount of the positive electrode active material. If the content of the Group 5 element and the Group 6 element is too small, the resistance increase rate increases, whereas if the content is too large, the cell life is reduced.
[0039] In this embodiment, the content of B may be in the range of 10 ppm to 3000 ppm, more specifically 50 ppm to 2000 ppm, even more specifically 100 ppm to 1000 ppm, and even more specifically 300 ppm to 800 ppm based on the total amount of the positive electrode active material. When the content of B satisfies the above range, the average crystal grain size may be reduced during firing of the positive electrode active material, and therefore the initial resistance and the resistance increase rate at high temperature of the positive electrode active material may be significantly reduced.
[0040] The LiOH content may be in the range of 100 ppm to 10000 ppm, more specifically 500 ppm to 7000 ppm, and even more specifically 1200 ppm to 3000 ppm based on the total amount of the positive electrode active material. When the LiOH content in the coating layer satisfies the above range, high capacity can be ensured and at the same time, life characteristics can be improved.
[0041] The content of Li2CO3 may be in the range of 1000 ppm to 5000 ppm, more specifically 1500 ppm to 4000 ppm, and even more specifically 2000 ppm to 3500 ppm based on the total amount of the positive electrode active material. When the content of Li2CO3 satisfies the above range, it is possible to improve excellent room temperature and high temperature life characteristics, and to reduce the resistance increase rate and the average leakage current value. At this time, the Li2CO3 is a compound resulting from the reaction of a metal raw material forming a lithium metal oxide with another raw material forming a coating layer, without adding a separate raw material forming a coating layer.
[0042] The content of Li2SO4 may be in the range of 10 ppm to 10,000 ppm, more specifically 80 ppm to 3,000 ppm, even more specifically 100 ppm to 2,000 ppm, even more specifically 100 ppm to 800 ppm, and even more specifically 100 ppm to 400 ppm, based on the total amount of the positive electrode active material. When the content of Li2SO4 satisfies the above range, excellent capacity characteristics can be ensured, while at the same time, life characteristics can be improved and initial resistance can be reduced.
[0043] As described above, the positive electrode active material of the present embodiment contains at least one of Group 5 and Group 6 elements, B, LiOH, Li2CO3, and Li2SO4 in the coating layer, so that the lithium secondary battery using this material exhibits excellent discharge capacity, improved initial efficiency, and excellent room temperature and high temperature life characteristics, and also significantly reduces the initial resistance and the resistance increase rate.
[0044] Such effects can be obtained when at least one of the Group 5 and Group 6 elements, B, LiOH, Li2CO3, and Li2SO4 are contained; if any one of these elements is not contained, the desired physical properties cannot be obtained.
[0045] Meanwhile, in the XPS analysis of the positive electrode active material of the embodiment of the present invention, a peak near 192.1 eV and a peak near 195.0 eV may exist, and a peak near 35.0 eV and a peak near 38.5 eV may also exist.
[0046] Meanwhile, in the EDS analysis of the positive electrode active material according to an embodiment of the present invention, the ratio of the relative intensities of Ni and W present at the boundaries of the primary particles satisfies the following formula 1:
[0047] [Formula 1] 0.1≦[I Ni / I W ]≦2.0
[0048] Here, I Ni is the relative intensity of Ni at the boundary of the primary particle, I W means the relative intensity of W present at the boundary of the primary grain.
[0049] More specifically, the lower limit of the formula 1 may be 0.2 or 0.4, and the upper limit may be 1.5, 1.0, or 0.8.
[0050] Meanwhile, in this embodiment, the content of nickel in the metal in the lithium metal oxide may be 85 mol % or more, more specifically, 88 mol % or more or 90 mol % or more.
[0051] When the nickel content in the metal in the lithium metal oxide is 80% or more as in this embodiment, a positive electrode active material with high output characteristics can be realized. The positive electrode active material of this embodiment having such a composition has a high energy density per volume, so that the capacity of the battery to which it is applied can be improved, and it is also suitable for use in electric vehicles.
[0052] According to another embodiment, a method for manufacturing a positive electrode active material includes the steps of: introducing a metal salt aqueous solution into a co-precipitation reactor to obtain a metal precursor; mixing the metal precursor, a lithium source material, and a doping source material to prepare a mixture; subjecting the mixture to a first heat treatment and then cooling; washing the product obtained in the cooling step with a material containing at least one of a Group 5 element and a Group 6 element; and drying the washed product, mixing it with a coating layer forming material, and subjecting it to a second heat treatment, wherein the coating layer forming material may include at least one of a Group 5 element and a Group 6 element, a boron compound, LiOH, and Li2SO4.
[0053] First, a step of obtaining a metal precursor is carried out by introducing an aqueous metal salt solution into a coprecipitation reactor.
[0054] More specifically, a metal precursor can be obtained by mixing a metal source material constituting a lithium metal oxide, for example, a nickel source material, a cobalt source material, a manganese source material, etc. with distilled water to prepare a metal salt aqueous solution, which is then introduced into a reactor and subjected to a coprecipitation process.
[0055] Next, the metal precursor, the lithium source material, and the doping source material are mixed to prepare a mixture.
[0056] The lithium metal oxide of this embodiment may be doped with elements such as Al. In this case, the lithium metal oxide may be prepared by adding doping materials so that the content of the doping elements is, for example, 3000 ppm to 4000 ppm Zr and 200 ppm to 350 ppm Al based on the total amount of the lithium metal oxide.
[0057] Zr ions occupy the Li site, and thus act as a kind of pillar, mitigating the contraction of the lithium ion path during the charge and discharge process, thereby stabilizing the layered structure. In addition, Al can stabilize the layered structure of the positive electrode active material. Therefore, the life characteristics of the lithium secondary battery can be further improved. Therefore, by including such a doping element, the life characteristics of the lithium secondary battery to which the positive electrode active material of this embodiment is applied can be further improved.
[0058] Then, the mixture is subjected to a first heat treatment and then cooled.
[0059] The first heat treatment may be performed, for example, at a temperature in the range of 700°C to 850°C. The time for the first heat treatment may be in the range of 3 hours to 40 hours. When the first heat treatment conditions satisfy the above ranges, the total amount of LiOH and Li2CO3, which are the residual lithium on the positive electrode surface, is less than 10,000 ppm, and the crystal grain size is in the range of 80 nm to 210 nm, so that a lithium secondary battery having excellent life and resistance characteristics and excellent thermal stability can be realized.
[0060] After the heat treatment, the fired body is cooled. Specifically, the cooling step can be carried out by a conventional method.
[0061] Next, the product produced in the cooling step is washed with a substance containing at least one of a group 5 element and a group 6 element.
[0062] The water washing is for removing residual lithium on the surface, and the reason for washing with a material containing at least one of group 5 and group 6 elements is to wet coat at least a portion of the surface of the primary particles or the surface of the secondary particles with at least one of group 5 and group 6 elements. In this case, the group 5 and group 6 elements may be W or Nb. By forming a coating layer using a wet coating method, not only the secondary particles but also the primary particles can be uniformly coated, thereby greatly reducing the rate of increase in resistance.
[0063] In this case, the W-containing material may be a mixture of distilled water or alcohol with at least one of ammonium meta-tungstate (AMT), ammonium para-tungstate, tungsten oxide, tungsten halide, tungsten hexaethoxide, tungsten i-propoxide, tungsten boride, tungsten nitride, and tungsten carbonyl. The concentration of the W-containing material may be 0.0001M to 0.1M, more specifically, 0.001M to 0.005M. If the concentration of the W-containing material is too low, the resistance increase rate is high, and if it is too high, the life characteristics are reduced.
[0064] In this case, the material containing Nb may be a mixture of distilled water or alcohol with at least one of ammonium niobium oxalate, niobium oxide, niobium nitride, niobium boride, niobium pentaethoxide, niobium i-propoxide, niobium n-propoxide, niobium i-butoxide, niobium n-butoxide, niobium halide, and niobium nitrate. The concentration of the Nb-containing substance may be 0.001 M to 0.5 M, more specifically 0.01 M to 0.2 M, even more specifically 0.025 M to 0.1 M, and even more specifically 0.025 M to 0.045 M. If the concentration of the Nb-containing substance is too low, there is a disadvantage that the resistance increase rate becomes high, and conversely, if it is too high, there is a disadvantage that the life characteristics are reduced.
[0065] Next, the washed product is dried, mixed with a coating layer forming material, and then subjected to a second heat treatment.
[0066] The drying step is for removing moisture from the surface of the washed positive electrode active material, and is carried out by a conventional method.
[0067] The second heat treatment may be performed at a temperature range of 200 to 450°C, and the heat treatment time may be in the range of 1 hour to 12 hours. This is an appropriate temperature and time range that does not impair high-temperature life characteristics. When the second heat treatment process satisfies these conditions, a coating layer containing at least one of group 5 elements and group 6 elements, B, LiOH, Li2CO3, and Li2SO4 is formed.
[0068] In the prepared positive electrode active material, the ranges of the contents of at least one of Group 5 elements and Group 6 elements, B, LiOH, Li2CO3, and Li2SO4 are the same as those described in the above embodiment, and therefore will not be repeated here.
[0069] Meanwhile, in this embodiment, the coating layer forming material includes a boron compound, LiOH, and Li2SO4. That is, the Li2CO3 contained in the coating layer of the finally obtained positive electrode active material is formed by an internal reaction of other raw materials added during the manufacturing process, and no separate raw materials are added.
[0070] The content of the boron compound in the coating layer forming material may be 300 ppm to 2000 ppm, more specifically 300 ppm to 1000 ppm, based on the entire coating layer forming material. When the content of the boron compound added as the coating layer forming material satisfies the above range, the crystal grain size of the positive electrode active material is in the range of 80 nm to 210 nm, and thus the positive electrode active material exhibits excellent thermal stability.
[0071] In this case, examples of the boron compound include H3BO3, boron oxides, boron compounds containing Li, BN, B4C, B2H6, B2F4, B2Cl4, B2Br4, and B2I4.
[0072] In addition, the content of LiOH contained in the coating layer forming material may be in the range of 10 ppm to 1000 ppm, more specifically 50 ppm to 700 ppm, and even more specifically 120 ppm to 300 ppm based on the entire coating layer forming material. When the content of LiOH added as the coating layer forming material satisfies the above range, it is possible to manufacture a slurry in a state that can be applied to an electrode during the manufacture of a positive electrode by suppressing the gelation phenomenon of the slurry caused by the residual lithium.
[0073] The content of Li2SO4 contained in the coating layer forming material may be in the range of 10 ppm to 500 ppm, more specifically 10 ppm to 200 ppm, even more specifically 10 ppm to 100 ppm, and more specifically 20 ppm to 5 ppm, based on the entire coating layer forming material. When the content of Li2SO4 added as the coating layer forming material satisfies the above range, a Li-BC-SO4-based ion conductor is formed on the surface, improving the mobility of lithium ions on the surface of the positive electrode active material, thereby realizing a lithium secondary battery having excellent life characteristics.
[0074] That is, in this example, the amount of LiOH and Li2SO4 added was less than the LiOH and Li2SO4 present in the coating layer of the final positive active material, which is believed to be due to the reaction of lithium and metal raw materials present in the lithium metal oxide during the secondary heat treatment process after adding the coating layer forming material.
[0075] The specific characteristics of the positive electrode active material prepared by the above method are the same as those described in the first embodiment, and therefore will not be described here.
[0076] The process conditions for producing the positive electrode active material of this embodiment will be described in more detail in the following examples.
[0077] In another embodiment of the present invention, there is provided a lithium secondary battery including a positive electrode including the positive electrode active material according to the embodiment of the present invention, a negative electrode including a negative electrode active material, and an electrolyte disposed between the positive electrode and the negative electrode.
[0078] The description regarding the positive electrode active material is the same as that of the above-described embodiment of the present invention, and therefore will be omitted.
[0079] The positive electrode active material layer may include a binder and a conductive material.
[0080] The binder serves to firmly adhere the positive active material particles to each other and to the current collector.
[0081] The conductive material is used to impart conductivity to the electrode, and in the battery being configured, any material that is an electron conductive material and does not cause a chemical change can be used.
[0082] The negative electrode includes a current collector and a negative electrode active material layer formed on the current collector, and the negative electrode active material layer contains a negative electrode active material.
[0083] Examples of the negative electrode active material include substances capable of reversibly intercalating / deintercalating lithium ions, lithium metal, alloys of lithium metal, substances capable of doping and undoping lithium, or transition metal oxides.
[0084] As the substance capable of reversibly intercalating / deintercalating lithium ions, any carbon-based negative electrode active material generally used in lithium ion secondary batteries can be used as a carbon material, and typical examples thereof include crystalline carbon, amorphous carbon, or a combination of these.
[0085] As the alloy of lithium metal, an alloy of lithium and a metal selected from the group consisting of Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, and Sn can be used.
[0086] Examples of the substance capable of doping and undoping lithium include Si, SiO x (0 < x < 2), Si-Y alloy (where Y is an element selected from the group consisting of alkali metals, alkaline earth metals, group 13 elements, group 14 elements, transition metals, rare earth elements, and combinations thereof and is not Si), Sn, SnO2, Sn-Y (where Y is an element selected from the group consisting of alkali metals, alkaline earth metals, group 13 elements, group 14 elements, transition metals, rare earth elements, and combinations thereof and is not Sn), and the like.
[0087] The transition metal oxide may include vanadium oxide, lithium vanadium oxide, etc. The negative electrode active material layer may also include a binder, and may optionally further include a conductive material.
[0088] The binder serves to firmly adhere the negative active material particles to each other and to the current collector.
[0089] The conductive material is used to impart electrical conductivity to the electrodes, and any material can be used as long as it does not cause a chemical change in the constructed battery and is electronically conductive.
[0090] The current collector may be selected from the group consisting of copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive metal, and combinations thereof.
[0091] The negative and positive electrodes are prepared by mixing an active material, a conductive material, and a binder in a solvent to prepare an active material composition, and then coating the composition on a current collector. Since such an electrode preparation method is widely known in the art, a detailed description thereof will be omitted in this specification. The solvent may be, but is not limited to, N-methylpyrrolidone.
[0092] The electrolyte includes a non-aqueous organic solvent and a lithium salt.
[0093] The non-aqueous organic solvent serves as a medium through which ions involved in the electrochemical reaction of the battery can migrate.
[0094] The lithium salt is a material that dissolves in an organic solvent and acts as a source of lithium ions in a battery to enable basic operation of a lithium secondary battery and promotes the movement of lithium ions between the positive electrode and the negative electrode.
[0095] Depending on the type of lithium secondary battery, a separator may be present between the positive and negative electrodes. As such a separator, polyethylene, polypropylene, polyvinylidene fluoride, or a multi-layer film of two or more layers of these may be used, and of course, a mixed multi-layer film such as a polyethylene / polypropylene two-layer separator, a polyethylene / polypropylene / polyethylene three-layer separator, or a polypropylene / polyethylene / polypropylene three-layer separator may be used.
[0096] Lithium secondary batteries can be classified into lithium ion batteries, lithium ion polymer batteries, and lithium polymer batteries depending on the type of separator and electrolyte used, into cylindrical, square, coin, pouch, etc. types depending on the shape, and into bulk and thin film types depending on the size. The structure and manufacturing method of these batteries are widely known in this field, so a detailed description will be omitted. EXAMPLES
[0097] The present invention will be described in more detail below with reference to examples. However, these examples are merely for the purpose of illustrating the present invention, and the present invention is not limited thereto.
[0098] "Production Example 1 - Production of Positive Electrode Active Material Precursor" (Ni 0.92 Co 0.04 Mn 0.04 The precursor with the composition of )(OH)2 was prepared by a conventional coprecipitation method.
[0099] Specifically, NiSO4·6H2O was used as the nickel source material, CoSO4·7H2O was used as the cobalt source material, and MnSO4·H2O was used as the manganese source material. These raw materials were dissolved in distilled water to produce metal salt aqueous solutions.
[0100] Next, after preparing the coprecipitation reactor, N2 was purged to prevent oxidation of metal ions during the coprecipitation reaction, and the reactor temperature was maintained at 50°C.
[0101] The coprecipitation reactor was charged with NH4(OH) as a chelating agent, and NaOH was used to adjust the pH.
[0102] The precipitate obtained by the coprecipitation process was filtered, washed with distilled water, and then dried in an oven at 100° C. for 24 hours to prepare a positive electrode active material precursor having an average particle size of 14.8 μm.
[0103] "Comparative Example 1 - Production of Ni 90% Positive Electrode Active Material" A mixture was prepared by uniformly mixing 1.05 mol of LiOH·H2O (Samchun Chemical, battery grade) and doping raw materials based on 1 mol of the positive active material precursor prepared in Preparation Example 1. In this case, ZrO2 (Aldrich, 3N) was used as the doping raw material so that Zr was 3,400 ppm, and Al(OH)3 (Aldrich, 4N) was used so that Al was 280 ppm.
[0104] The mixture was placed in a tube furnace and calcined while oxygen was flowed in at 200 mL / min. The calcination process was performed by first heat-treating at 480° C. for 5 hours, then heating to 760° C. at a heating rate of 5° C. / min and maintaining the temperature for 16 hours. The product after the calcination process was naturally cooled to 25° C. to prepare a cathode active material.
[0105] "Comparative Example 2 - 90% Ni positive electrode active material containing 500 ppm W" A mixture was prepared by uniformly mixing 1.05 mol of LiOH·H2O (Samchun Chemical, battery grade) and doping raw materials based on 1 mol of the positive active material precursor prepared in Preparation Example 1. In this case, ZrO2 (Aldrich, 3N) was used as the doping raw material so that Zr was 3,400 ppm, and Al(OH)3 (Aldrich, 4N) was used so that Al was 280 ppm.
[0106] The mixture was placed in a tube furnace and calcined while oxygen was flowing in at 200 mL / min. The calcination process was performed by first heat-treating at 480°C for 5 hours, then heating to 760°C at a heating rate of 5°C / min and maintaining the temperature for 16 hours. The product after the calcination process was then naturally cooled to 25°C.
[0107] Next, the cooled product was washed with distilled water mixed with 0.002M ammonium meta-tungstate (AMT), filtered, and dried to produce a positive electrode active material with a tungsten (W) surface coating.
[0108] "Comparative Example 3-B: 90% Ni positive electrode active material containing 500 ppm" The cooled product was washed with distilled water and distilled water not containing AMT, filtered and dried, and then dry-mixed with 500 ppm of H3BO3 (Aldrich). The mixture was then subjected to a second heat treatment at 280°C for 5 hours in the same manner as in Comparative Example 2, except that a coating layer containing 500 ppm of B was formed on the surface of the cooled product.
[0109] "Comparative Example 4 - 90% Ni positive electrode active material containing 1700 ppm LiOH and 3000 ppm Li2CO3" A positive electrode active material having a coating layer containing 1700 ppm LiOH and 3000 ppm Li2CO3 formed on the surface was prepared in the same manner as in Comparative Example 3, except that the cooled product was dry-mixed with 250 ppm LiOH based on Li and then subjected to a second heat treatment.
[0110] "Comparative Example 5 - Ni 90% positive electrode active material containing 1700 ppm LiOH, 3000 ppm Li2CO3, and 300 ppm Li2SO4" The cooled product was dry-mixed with 250 ppm LiOH and 30 ppm Li2SO4 based on Li and S, and then subjected to a second heat treatment in the same manner as in Comparative Example 3, to prepare a positive active material having a coating layer containing 1700 ppm LiOH, 3000 ppm Li2CO3, and 500 ppm Li2SO4 on the surface.
[0111] "Example 1-B 500 ppm, W 500 ppm, LiOH 1700 ppm, Li2CO3 3000 ppm, Li2SO4 300 ppm containing 90% Ni positive electrode active material" The cooled product was dry-mixed with 500 ppm H3BO, 250 ppm LiOH, and 30 ppm Li2SO4 based on Li and S, and then subjected to a second heat treatment in the same manner as in Comparative Example 2 to prepare a positive active material having a coating layer containing 500 ppm W, 500 ppm B, 1700 ppm LiOH, 3000 ppm Li2CO3, and 300 ppm Li2SO4 on the surface.
[0112] "Example 2-1 - Preparation of Ni 90% positive electrode material containing W 10 ppm, B 500 ppm, LiOH 1700 ppm, Li2CO3 3000 ppm, and Li2SO4 300 ppm" (Ni 0.92 Co 0.04 Mn 0.04 The precursor with the composition )(OH)2 was prepared by mixing LiOH·H2O (Samchun Chemical, battery grade) in a molar ratio of 1:1.05, ZrO2 (Aldrich, 4N) to give 3,400 ppm Zr, and Al(OH)3 (Aldrich, 4N) to give 280 ppm Al, and then charged into a tube furnace (inner diameter 50 mm, length 1,000 mm) and fired while injecting oxygen at 200 mL / min. The firing conditions were 480°C for 5 h, then 700-750°C for 16 h, with a heating rate of 5°C / min.
[0113] After cooling to room temperature, the sintered material was crushed and classified to produce the cathode material. Using 200g of cathode material as a base, the cathode powder was washed with a mixture of 100g of distilled water (DI water) and 0.002M of ammonium meta-tungstate (AMT), filtered, and dehydrated using a filter press. The recovered cathode material was dried at 80°C for 12 hours, and mixed with 500ppm of H3BO3, 250ppm of LiOH, and 30ppm of Li2SO4 in a mixer, and then subjected to a secondary heat treatment at 280°C to produce the cathode material.
[0114] "Example 2-2 - Preparation of Ni 90% positive electrode material containing W 50 ppm, B 500 ppm, LiOH 1700 ppm, Li2CO3 3000 ppm, and Li2SO4 300 ppm" A positive electrode material was prepared in the same manner as in Example 2-1, except that AMT was dissolved at 0.0002M in the water washing process and washed with water.
[0115] "Example 2-3 - Preparation of Ni 90% positive electrode material containing W 100 ppm, B 500 ppm, LiOH 1700 ppm, Li2CO3 3000 ppm, and Li2SO4 300 ppm" A positive electrode material was prepared in the same manner as in Example 2-1, except that AMT was dissolved at 0.0005M in the water washing process and washed with water.
[0116] "Example 2-4 - Preparation of Ni 90% positive electrode material containing W 1000ppm, B 500ppm, LiOH 1700ppm, Li2CO3 3000ppm, and Li2SO4 300ppm" A cathode material was prepared in the same manner as in Example 2-1, except that AMT was dissolved at 0.01M in the water washing process and washed with water.
[0117] "Example 2-5 - Preparation of Ni 90% cathode material containing W 3000ppm, B 500ppm, LiOH 1700ppm, Li2CO3 3000ppm, and Li2SO4 300ppm" A positive electrode material was prepared in the same manner as in Example 2-1, except that AMT was dissolved at 0.05M in the water washing process and washed with water.
[0118] "Example 2-6 - Preparation of Ni 90% positive electrode material containing W 10000ppm, B 500ppm, LiOH 1700ppm, Li2CO3 3000ppm, and Li2SO4 300ppm" A positive electrode material was prepared in the same manner as in Example 2-1, except that AMT was dissolved at 0.5M in the water washing process and washed with water.
[0119] "Example 3-1 - Preparation of Ni 90% cathode material containing W 500ppm, B 500ppm, LiOH 1700ppm, Li2CO3 3000ppm, and Li2SO4 10ppm" (Ni 0.92 Co 0.04 Mn 0.04 The precursor with the composition of )(OH)2 was prepared by mixing LiOH·H2O (Samchun Chemical, battery grade) in a molar ratio of 1:1.05, ZrO2 (Aldrich, 4N) to make Zr 3,400ppm, and Al(OH)3 (Aldrich, 4N) to make Al 280ppm, and then charged into a tube furnace (inner diameter 50mm, length 1,000mm) and fired while injecting oxygen at 200mL / min. The firing conditions were 480℃ for 5h, then 700~750℃ for 16h, with a heating rate of 5℃ / min.
[0120] After cooling to room temperature, the sintered material was crushed and classified to produce the cathode material. Using 200g of cathode material as a base, the cathode powder was washed with a mixture of 100g of distilled water (DI water) and 0.002M of ammonium meta-tungstate (AMT), filtered, and dehydrated using a filter press. The recovered cathode material was dried at 80℃ for 12 hours, and then mixed with 500ppm of H3BO3, 250ppm of LiOH, and 10ppm of Li2SO4 in a mixer, and then subjected to a secondary heat treatment at 280℃ to produce the cathode material.
[0121] "Example 3-2 - Preparation of Ni 90% cathode material containing W 500ppm, B 500ppm, LiOH 1700ppm, Li2CO3 3000ppm, and Li2SO4 100ppm" A positive electrode material was prepared in the same manner as in Example 3-1, except that 500 ppm of B, 250 ppm of LiOH, and 20 ppm of Li2SO4 were added.
[0122] "Example 3-3 - Preparation of Ni 90% positive electrode material containing W 500 ppm, B 500 ppm, LiOH 1700 ppm, Li2CO3 3000 ppm, and Li2SO4 500 ppm" A positive electrode material was prepared in the same manner as in Example 3-1, except that 500 ppm of B, 250 ppm of LiOH, and 60 ppm of Li2SO4 were added.
[0123] "Example 3-4 - Preparation of Ni 90% positive electrode material containing W 500ppm, B 500ppm, LiOH 1700ppm, Li2CO3 3000ppm, and Li2SO4 1000ppm" A positive electrode material was prepared in the same manner as in Example 3-1, except that 500 ppm of B, 250 ppm of LiOH, and 120 ppm of Li2SO4 were added.
[0124] "Example 3-5 - Preparation of Ni 90% positive electrode material containing W 500ppm, B 500ppm, LiOH 1700ppm, Li2CO3 3000ppm, and Li2SO4 3000ppm" A cathode material was prepared in the same manner as in Example 3-1, except that 500 ppm of B, 250 ppm of LiOH, and 250 ppm of Li2SO4 were added.
[0125] "Example 4-1 - Preparation of Ni 90% cathode material containing W 500ppm, B 500ppm, LiOH 100ppm, Li2CO3 3000ppm, and Li2SO4 300ppm" The cathode material was prepared in the same manner as in Example 1, except that 50 ppm of LiOH was added.
[0126] "Example 4-2 - Preparation of Ni 90% positive electrode material containing W 500ppm, B 500ppm, LiOH 1000ppm, Li2CO3 3000ppm, and Li2SO4 300ppm" The cathode material was prepared in the same manner as in Example 1, except that 100 ppm of LiOH was added.
[0127] "Example 4-3 - Preparation of Ni 90% positive electrode material containing W 500ppm, B 500ppm, LiOH 5000ppm, Li2CO3 3000ppm, and Li2SO4 300ppm"
[0128] The cathode material was prepared in the same manner as in Example 1, except that 500 ppm of LiOH was added.
[0129] "Example 4-4-Manufacture of Ni 90% positive electrode material containing W 500 ppm, B 500 ppm, LiOH 10000 ppm, Li2CO3 3000 ppm, and Li2SO4 300 ppm" The cathode material was prepared in the same manner as in Example 1, except that 1000 ppm of LiOH was added.
[0130] "Example 5-1 - Preparation of Ni 90% cathode material containing W 500ppm, B 500ppm, LiOH 1700ppm, Li2CO3 3000ppm, and Li2SO4 300ppm" The cathode material was prepared in the same manner as in Example 1, except that the second heat treatment temperature was 200°C.
[0131] "Example 5-2: Preparation of Ni 90% cathode material containing W 500ppm, B 500ppm, LiOH 1700ppm, Li2CO3 3000ppm, and Li2SO4 300ppm" The cathode material was prepared in the same manner as in Example 1, except that the second heat treatment temperature was 220°C.
[0132] "Example 5-3 - Preparation of Ni 90% cathode material containing W 500ppm, B 500ppm, LiOH 1700ppm, Li2CO3 3000ppm, and Li2SO4 300ppm" The cathode material was prepared in the same manner as in Example 1, except that the second heat treatment temperature was 240°C.
[0133] "Example 5-4 - Preparation of Ni 90% positive electrode material containing W 500ppm, B 500ppm, LiOH 1700ppm, Li2CO3 3000ppm, and Li2SO4 300ppm" The cathode material was prepared in the same manner as in Example 1, except that the second heat treatment temperature was 260°C.
[0134] "Example 5-5-Manufacture of Ni 90% cathode material containing W 500ppm, B 500ppm, LiOH 1700ppm, Li2CO3 3000ppm, and Li2SO4 300ppm" The cathode material was prepared in the same manner as in Example 1, except that the second heat treatment temperature was 300°C.
[0135] "Example 5-6 - Preparation of Ni 90% cathode material containing W 500ppm, B 500ppm, LiOH 1700ppm, Li2CO3 3000ppm, and Li2SO4 300ppm" The cathode material was prepared in the same manner as in Example 1, except that the second heat treatment temperature was 450°C.
[0136] "Example 6-1 - Preparation of Ni 90% positive electrode material containing 10 ppm Nb, 500 ppm B, 1700 ppm LiOH, 3000 ppm Li2CO3, and 300 ppm Li2SO4" The cathode material was prepared in the same manner as in Example 1, except that in the water washing process, 0.005M of ammonium niobium oxalate was dissolved as a Nb source instead of ammonium meta tungstate (AMT) and washed with water.
[0137] "Example 6-2 - Preparation of Ni 90% cathode material containing 50 ppm Nb, 500 ppm B, 1700 ppm LiOH, 3000 ppm Li2CO3, and 300 ppm Li2SO4" The cathode material was prepared in the same manner as in Example 1, except that in the water washing process, 0.01M ammonium niobium oxalate was dissolved as a Nb source instead of ammonium meta tungstate (AMT) and washed with water.
[0138] "Example 6-3 - Preparation of Ni 90% positive electrode material containing 100 ppm Nb, 500 ppm B, 1700 ppm LiOH, 3000 ppm Li2CO3, and 300 ppm Li2SO4" The cathode material was prepared in the same manner as in Example 1, except that in the water washing process, 0.02M of ammonium niobium oxalate was dissolved as a Nb source instead of ammonium meta tungstate (AMT) and washed with water.
[0139] "Example 6-4 - Preparation of Ni 90% positive electrode material containing 500 ppm Nb, 500 ppm B, 1700 ppm LiOH, 3000 ppm Li2CO3, and 300 ppm Li2SO4" The cathode material was prepared in the same manner as in Example 1, except that in the water washing process, 0.03M of ammonium niobium oxalate was dissolved as a Nb source instead of ammonium meta tungstate (AMT) and washed with water.
[0140] "Example 6-5 - Preparation of Ni 90% cathode material containing 1000ppm Nb, 500ppm B, 1700ppm LiOH, 3000ppm Li2CO3, and 300ppm Li2SO4" The cathode material was prepared in the same manner as in Example 1, except that in the water washing process, 0.05M of ammonium niobium oxalate was dissolved as a Nb source instead of ammonium meta tungstate (AMT) and washed with water.
[0141] "Example 6-6 - Preparation of Ni 90% positive electrode material containing 3000ppm Nb, 500ppm B, 1700ppm LiOH, 3000ppm Li2CO3, and 300ppm Li2SO4" The cathode material was prepared in the same manner as in Example 1, except that in the water washing process, 0.1M ammonium niobium oxalate was dissolved as a Nb source instead of ammonium meta tungstate (AMT) and washed with water.
[0142] "Example 6-7 - Preparation of Ni 90% cathode material containing 10000ppm Nb, 500ppm B, 1700ppm LiOH, 3000ppm Li2CO3, and 300ppm Li2SO4" The cathode material was prepared in the same manner as in Example 1, except that in the water washing process, 0.3M of ammonium niobium oxalate was dissolved as a Nb source instead of ammonium meta tungstate (AMT) and washed with water.
[0143] (Experimental Example 1) Evaluation of electrochemical performance (1) Manufacturing of coin-type half cells Coin-type half cells were manufactured using the positive electrode active materials manufactured in Example 1, Examples 2-1 to 2-6, Examples 3-1 to 3-5, Examples 4-1 to 4-4, Examples 5-1 to 5-6, Examples 6-1 to 6-7, and Comparative Examples 1 to 5.
[0144] Specifically, the positive electrode active material, Denka Black conductive material, and polyvinylidene fluoride binder (product name: KF1100) were mixed in a weight ratio of 92.5:3.5:4, and this mixture was added to an N-Methyl-2-pyrrolidone solvent so that the solid content was approximately 30% by weight, to prepare a positive electrode active material slurry.
[0145] The slurry was coated on an aluminum foil (thickness: 15 μm) as a positive electrode current collector using a doctor blade, dried, and rolled to prepare a positive electrode. The loading amount of the positive electrode was 14.6 mg / cm 2 and the rolling density is 3.1 g / cm 3 It was.
[0146] A 2032 coin-type half cell was fabricated in a conventional manner using the positive electrode, lithium metal negative electrode (200 μm, Honzo metal), electrolyte, and polypropylene separator. The electrolyte was a mixed solution of 1M LiPF6 dissolved in a mixed solvent of ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate (EMC) (mixture ratio EC:DMC:EMC = 3:4:3 vol%) and 1.5% VC added.
[0147] (2) Evaluation of 25℃, 0.1C discharge capacity and room temperature initial resistance The coin-type half cell prepared in (1) above was aged at room temperature (25° C.) for 10 hours, and then a charge / discharge test was performed.
[0148] The capacity evaluation was performed with 215mAh / g as the reference capacity, and the charge / discharge conditions were CC / CV 2.5-4.25V with 1 / 20C cut-off. The initial capacity was measured under 0.1C charge / 0.1C discharge conditions.
[0149] The resistance was calculated by measuring the voltage fluctuation for 60 seconds after applying a 0.2C discharge current at 4.25V charge 100% at 0.2C. The results are shown in Table 1 below.
[0150] (3) Evaluation of 45℃ life and resistance increase rate The high temperature cycle life characteristics were measured by measuring the ratio of the 30th capacity to the initial capacity after 30 measurements under the condition of 0.3C charge / 0.3C discharge at high temperature (45℃), and the resistance was calculated by measuring the voltage fluctuation 60 seconds after applying a discharge current at 100% charge of 4.25V.
[0151] The resistance increase rate was calculated by measuring the resistance at a high temperature (45°C) in the same manner as the initial resistance measurement method after 30 cycles of cycle life (high temperature initial resistance) and converting the increase rate into a percentage (%). The measurement results are shown in Table 2 below.
[0152] [Table 1]
[0153] [Table 2]
[0154] Table 1 shows the measurement results of initial efficiency and initial resistance at room temperature for the positive electrode active materials produced by Example 1, Examples 2-1 to 2-6, Examples 3-1 to 3-5, Examples 4-1 to 4-4, Examples 5-1 to 5-6, Examples 6-1 to 6-7, and Comparative Examples 1 to 5.
[0155] Table 2 shows the measurement results of high-temperature life and resistance increase rate for the positive electrode active materials produced by Example 1, Examples 2-1 to 2-6, Examples 3-1 to 3-5, Examples 4-1 to 4-4, Examples 5-1 to 5-6, Examples 6-1 to 6-7, and Comparative Examples 1 to 5.
[0156] Referring to Tables 1 and 2, it can be seen that the positive electrode active materials according to Example 1, Examples 2-1 to 2-6, Examples 3-1 to 3-5, Examples 4-1 to 4-4, Examples 5-1 to 5-6, Examples 6-1 to 6-7, and Comparative Examples 1 to 5, in which the coating layer contains W or Nb, B, LiOH, Li2CO3, and Li2SO4, generally have improved initial capacity and high-temperature life characteristics, and the initial and high-temperature resistances and resistance increase rates are all decreased, compared to the positive electrode active materials according to Comparative Examples 1 to 5 in which no coating layer is formed or in which a coating layer not containing any W or Nb, B, LiOH, Li2CO3, or Li2SO4 is formed.
[0157] (Experimental Example 2) TEM analysis of positive electrode active material The positive electrode active material prepared in Example 1 was analyzed by a Transmission Electron Microscope (TEM) / Energy Dispersive X-Ray Spectrometer (EDS), and the results are shown in FIGS. 1 and 2.
[0158] The results in Figure 1 show that tungsten penetrates between the primary particles and forms a coating layer.
[0159] FIG. 2 shows a cross-sectional EDS line profile image of Example 1, which shows that W is uniformly distributed among the primary particles of the cathode material.
[0160] At this time, it was confirmed from the EDS line profile results that the ratio of the absolute intensity values of the Ni and W peaks (INi / IW) was approximately 0.60.
[0161] (Experimental Example 3) XPS analysis of positive electrode active material The positive electrode active material prepared in Example 1 was analyzed by XPS (X-ray Photoelectron Spectroscopy) and the results are shown in FIG. 3 and Table 3 below. 3+ , W 6+ That is, FIG. 3 and Table 3 relate to the XPS B1s and W4f peak analyses of Example 1, B2O3, and WO3, and in the case of Example 1, the formation of new phases was confirmed at B1s (195.0 eV) and W4f (38.5 eV).
[0162] [Table 3]
[0163] FIG. 4 is a graph showing the change in discharge capacity depending on the W content in Example 1 and Examples 2-1 to 2-6.
[0164] Referring to FIG. 4, it can be seen that the capacity is the largest when W is 500 ppm.
[0165] FIG. 5 is a graph showing the change in DC-IR depending on the W content in Example 1 and Examples 2-1 to 2-6.
[0166] Referring to FIG. 5, it can be seen that the initial resistance is the lowest optimum point when W is 500 ppm.
[0167] FIG. 6 is a graph showing the change in DCIR increase rate depending on the W content in Example 1 and Examples 2-1 to 2-6.
[0168] Referring to FIG. 6, it can be seen that the resistance increase rate is smallest when W is 500 ppm.
[0169] FIG. 7 is a graph showing the initial discharge capacity as a function of the LiOH content in Example 1 and Examples 4-1 to 4-4.
[0170] Referring to FIG. 7, it can be seen that the discharge capacity is highest when the LiOH content is 1700 ppm.
[0171] FIG. 8 is a diagram showing the change in discharge capacity depending on the Li2SO4 content in Example 1 and Examples 3-1 to 3-5.
[0172] Referring to FIG. 8, it can be seen that when the content of Li2SO4 is 300 ppm, the discharge capacity is the highest.
[0173] The present invention is not limited to the embodiments, and can be manufactured in various different forms, and a person skilled in the art to which the present invention belongs can understand that the present invention can be embodied in other specific forms without changing the technical idea or essential features of the present invention. Therefore, it should be understood that the above embodiment is illustrative in all respects and not limiting.
Claims
1. Lithium metal oxide particles; and The lithium metal oxide particles include a coating layer located on at least a portion of the surface thereof, The coating layer contains at least one of Group 5 and Group 6 elements, B, LiOH, Li 2 CO 3 and Li 2 SO 4 A positive electrode active material for a lithium secondary battery comprising:
2. The positive electrode active material is in the form of secondary particles including a plurality of primary particles, The positive electrode active material for a lithium secondary battery according to claim 1 , wherein at least one of the Group 5 element and the Group 6 element is located on at least a portion of the surface of the primary particle.
3. The positive electrode active material for a lithium secondary battery according to claim 1 , wherein the Group 5 element includes Nb.
4. The positive electrode active material for a lithium secondary battery according to claim 1 , wherein the Group 6 element includes W.
5. 2. The positive electrode active material for lithium secondary batteries according to claim 1, wherein the content of the Group 5 element and the Group 6 element is 10 ppm to 10,000 ppm based on the entire positive electrode active material.
6. 2. The positive electrode active material for a lithium secondary battery according to claim 1, wherein the content of the LiOH is 100 ppm to 10,000 ppm based on the total amount of the positive electrode active material.
7. The Li 2 SO 4 The positive electrode active material for lithium secondary batteries according to claim 1, wherein the content of is 10 ppm to 3000 ppm based on the entire positive electrode active material.
8. The positive electrode active material was analyzed by XPS.
2. The positive electrode active material for a lithium secondary battery according to claim 1, wherein a peak is present near 192.1 eV and a peak is present near 195.0 eV, and a peak is present near 35.0 eV and a peak is present near 38.5 eV.
9. The positive electrode active material was found to have the following properties when analyzed by EDS: The positive electrode active material for a lithium secondary battery according to claim 2 , wherein a ratio of relative intensities of Ni and W present at the boundaries of the primary particles satisfies the following formula 1: [Formula 1] 0.1≦[I Ni / I W ]≦2.0 (Here, I Ni is the relative intensity of Ni present at the boundary of the primary particle, I W means the relative intensity of W present at the boundary of the primary particle.)
10. 2. The positive electrode active material for a lithium secondary battery according to claim 1, wherein the content of nickel in the metal within the lithium metal oxide particles is 85 mol % or more.
11. Introduction of an aqueous metal salt solution into a coprecipitation reactor to obtain a metal precursor; mixing the metal precursor, a lithium source material, and a doping source material to prepare a mixture; subjecting the mixture to a first heat treatment and then cooling; washing the product obtained in the cooling step with a substance containing at least one of a Group 5 element and a Group 6 element; and the washed product is dried, mixed with a coating layer forming material, and subjected to a second heat treatment to obtain lithium metal oxide particles having a coating layer formed thereon; Including, The coating layer forming material is a boron compound, LiOH and Li 2 SO 4 The method for producing a positive electrode active material for a lithium secondary battery includes the steps of:
12. In the water washing step, The substance containing a Group 5 element is At least one of distilled water and alcohol; and Ammonium niobium oxalate, niobium oxide, niobium nitride, niobium boride, niobium pentaethoxide, niobium i-propoxide, niobium n-propoxide, niobium i-butoxide, niobium n-butoxide, niobium halide The method for producing a positive electrode active material for a lithium secondary battery according to claim 11, wherein the positive electrode active material is a mixture of at least one of niobium halide and niobium nitrate.
13. In the water washing step, The group 6-containing substance is At least one of distilled water and alcohol; and 12. The method for producing a positive electrode active material for a lithium secondary battery according to claim 11, wherein the positive electrode active material is a mixture of at least one of ammonium meta-tungstate (AMT), ammonium para-tungstate, tungsten oxide, tungsten halide, tungsten hexaethoxide, tungsten i-propoxide, tungsten boride, tungsten nitride, and tungsten carbonyl.
14. The method for producing a positive electrode active material for a lithium secondary battery according to claim 11, wherein the second heat treatment is performed at a temperature in the range of 200 to 450°C.
15. A method for producing a positive electrode active material for a lithium secondary battery as described in claim 11, wherein the coating layer contains one or more of group 5 elements and group 6 elements, B, LiOH, Li 2 CO 3 and Li 2 SO 4 , and the Li 2 CO 3 is not separately added as a lithium raw material but is the result of an internal reaction.
16. A positive electrode comprising the positive electrode active material according to any one of claims 1 to 10; A negative electrode; and Nonaqueous electrolyte A lithium secondary battery comprising:
Citation Information
Patent Citations
Positive electrode material for nonaqueous electrolyte lithium ion secondary battery and its manufacturing method
JP2006073482A
Positive electrode active material for rechargeable lithium battery, method for menufacturing the same, and rechargeable lithium battery including the same
KR1020170075596A